Human resource management, social innovation and technology - Bondarouk, Tanya, 1967-; Olivas-Lujan, Miguel R. (Advanced series in management ;, 2014)
This volume places social innovation between human resource management (HRM) and technology. There is a growing acceptance of the theory that HRM is strategically important for social innovation within organizations. To meet the requirements of globalization, diversity, "war for talent", and fast technological developments, HRM should allow a greater amount of flexibility and innovation in their policies and practices. In order for this to happen, however, HRM needs to be modernised by replacing inefficient and unsustainable HR practices and forms with flexible, sound, and pioneering ones, crossing inter- and intra-organizational boundaries. Built within the Social Innovation research tradition, this volume views innovation of HRM from two ends of one continuum: At one end, HR practices and policies should be designed to support innovative organizational members, the creation of new ideas, an innovative organizational climate, and enlargement of the innovation capacity of organizations. At the other end, the HRM function evolves through applying new structures and new channels for delivery of the HR practices, and through involving new agents in the management of Human Resources.